Gender, crime, and criminal justice - Walklate, Sandra (Willan, 2001)
This book provides a lucid and highly accessible introduction to gender issues in crime and criminal justice, central to any understanding of crime and criminal justice policy. It deals with a wide range of issues within criminology and victimology from the way in which the fear of crime is debated to the way in which the law operates in a gendered fashion. It replaces and updates her earlier book "Gender and Crime: An Introduction" (1995). "Gender, Crime and Criminal Justice" is divided into three main sections, addressing theoretical issues (especially masculinity and feminism); substantive issues (looking particularly at the relationship between risk, criminality and masculinity, and sexual violence); and questions of policy, examining gender in the criminal justice professions, and in government criminal justice policy. The book concludes with an overview of the themes raised in the book, special attention being paid to recent work on the unhappy juxtaposition of sex, race and class. List price: ₹1,824.05 Currently unavailable AbeBooks may have this title (opens in new window). Product details